2019
DOI: 10.1371/journal.pone.0215507
|View full text |Cite
|
Sign up to set email alerts
|

Evolving understanding of cardiovascular, cerebrovascular and peripheral arterial disease in people living with HIV and role of novel biomarkers. A study of the Spanish CoRIS cohort, 2004-2015

Abstract: Objectives To analyze the incidence rates (IR) and spectrum of vascular events in people living with HIV (PLWH) in Spain from 2004 to 2015. Serial measurements of different plasma cardiovascular biomarkers were assessed in relation to disease development. Methods Longitudinal study in a nationwide contemporary multicenter cohort of PLWH. A nested case-control study was performed to evaluate the predictive value of cardiovascular biomarkers. Additive generalized and Cox … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
(52 reference statements)
1
5
0
Order By: Relevance
“…In Iceland and Israel, the annual incidence of intermittent claudication was 0.1% and 1.0% [6], and among men in the Netherlands in age groups comparable to those of our cohort, the annual incidence of ABI <0.95 per 1000 person-years was 1.7 and 1.5 for those aged 40-54 years and 55-64 years, respectively [29]. In previous registry studies examining PAD in PWH, incidence rate estimates ranged from 0.19 to 3.17 per 1000 person-years [15][16][17]30]. Notably, a study from the Veterans Ageing Cohort Study (VACS) found an incidence of 11.9 per 1000 person-years corresponding to a cumulative 2.5-year PAD incidence of around 2% [18].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In Iceland and Israel, the annual incidence of intermittent claudication was 0.1% and 1.0% [6], and among men in the Netherlands in age groups comparable to those of our cohort, the annual incidence of ABI <0.95 per 1000 person-years was 1.7 and 1.5 for those aged 40-54 years and 55-64 years, respectively [29]. In previous registry studies examining PAD in PWH, incidence rate estimates ranged from 0.19 to 3.17 per 1000 person-years [15][16][17]30]. Notably, a study from the Veterans Ageing Cohort Study (VACS) found an incidence of 11.9 per 1000 person-years corresponding to a cumulative 2.5-year PAD incidence of around 2% [18].…”
Section: Discussionsupporting
confidence: 64%
“…Few studies have investigated the incidence of PAD in PWH. These studies were retrospective and based on registry data or patient records, thereby excluding subclinical cases and underestimating the disease burden [15][16][17][18][19]. It remains to be determined to what extent traditional risk factors contribute to the risk of PAD, and whether HIV-related risk factors are involved in the PAD pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…We diagnosed a total of 43 strokes, excluding transient ischemic attacks (that were also excluded by Crane et al), which corresponded to a global incidence rate of 1.9 cases per 1000 patient-year, like the ones reported by other authors in our country. 2 This incidence has progressively increased during time, starting from 0.63 cases per 1000 patient-year during the 1993–2006 period to 3.3 cases per 1000 patient-year during the 2013–2017 period. The mean age of patients was 51 years, and 81% were men.…”
mentioning
confidence: 99%
“…To further test this hypothesis, tissue evaluation of the IA, particularly in secondary lymphoid organs, and functional assays would be necessary. According to this model, the fact that we have shown that residual viremia is associated with a marker of monocyte activation (sCD14), two markers of endothelial activation (sEPCR and tPA), and a marker of coagulation (D-dimer), three forms of activation known to favor atherothrombosis (33)(34)(35), should encourage us to search for a link between residual viremia and atherosclerosis.…”
Section: Discussionmentioning
confidence: 98%